Inhibitors to Earth-based Materials Adoption in Urban Housing Construction: The View of Design Experts - Nwaki, William; Sofolahan, Onyinye; Eze, Emmanuel (Tecno Scientifica Publishing & Society of Tropical Science and Technology, 2023)
Earth-based materials are eco-friendly and harmless to the environment but have been neglected and relegated, and preference is given to non-sustainable and expensive conventional materials owing to certain factors. Existing studies in the Nigerian context did not consider the factors hindering the use of earthen materials in urban low-cost housing production. This study presents the outcome of examining the inhibitors to the adoption of earth-based materials in urban housing construction from the perspective of design experts in a developing country like Nigeria. Thus, it fills the critical literature gap in the Nigerian context. A well-structured quantitative questionnaire was utilised to collect data from construction design experts using the snowball sampling technique via electronic means. With a reliability index of 0.899, The gathered data were analysed using frequencies, percentages, Mean score, normalisation value technique, Mann-Whitney U test, overlap analysis, and exploratory factor analysis (EFA). It was found that the major barriers to the use of earth materials in urban housing production are (i) image and aesthetic barriers, (ii) Knowledge and resistance barriers, (iii) technology and data barriers, (iv) strength and maintenance barriers, and (v) demand and demographic barriers. More training and workshops were advocated to increase knowledge of the environmental and economic benefits of these materials among stakeholders to influence their interest and the market for earthen materials' acceptability and usage in housing production in urban areas.